Improved production technology of jute and mesta in India: An overview - Ghorai, A K; Mitra, Sabyasachi; Mahapatra, B S (Indian Farming, 2015)
During 1950-51, 3.31 million bales of jute and mesta fibre was produced from 0.57 million hecatre area with an average productivity of 10.43 q/ha and the corresponding figures for 2006-07 were 0.9 million hectares, 10.4 million blaes and 22.4 q/ha, respectivity. The productivity of jute had more than doubled over the last five decades and adoption of high-yielding and premature flowering resistant varieties of jute along with judicious crop husbandry were the key factors behind this significant achievements.